Soil erosion and sediment yield at construction site - a case study - Law, Dah Lit (Universiti Malaysia Sarawak, (UNIMAS), 2012)
In this research, soil erosion and sediment assessments were carried out for cut-and-fill activities at Samalaju Industrial Park, Bintulu, Sarawak. In this research, two equations called Revised Universal Soil Loss Equation (RUSLE) and Modified Universal Soil Loss Equation (MUSLE) equations were used to provide as assessment on soil erosion and sediment yield during pre-construction, during-construction and post-construction periods.